Sistem Monitoring Suhu dan Kelembaban Portable Berbasis IoT menggunakan Arduino Mega dan ESP32 - Prasepvianto Estu Broto (Prodi Sistem Informasi UIN Alauddin, 2023)
The Internet of Things (IoT) is no longer a foreign concept. All devices have started to use IoT technology to connect with each other, allowing for remote and real-time monitoring. In this research, portable IoT-based temperature and humidity monitoring was conducted. The research was divided into three stages: hardware design, software design, and device performance testing. The system was designed using an Arduino Mega microcontroller for data acquisition and an ESP32 as a web server to display data from the Arduino Mega. The temperature and humidity sensor used was the DHT21. The RTC DS3231 was used as a timer to facilitate the analysis of the readings. The results of the sensor and RTC readings were displayed on an LCD and web server and stored on a microSD for further analysis. The results of the system testing showed that the system can be used for portable temperature and humidity measurement and real-time monitoring of the readings through a web server from multiple devices simultaneously.